The Effect of Knowledge and Understanding of Bahasa Indonesia toward Personal, Professional, and Social Competency of University Students - Aniati, Aniati; Lumbantoruan, Jitu Halomoan; Arifin, Syaadiah; Nurfaizah, Andi; Sartika, Andi Dian (FKIP Universitas Lampung, 2024)
Abstract: The fact is that 38% of students are satisfied and 50% are less satisfied with Indonesian language competency. Another fact, out of 30,564 there are 82.59% categories of sufficient, weak, and very weak language knowledge. Urgency is researched because there is a gap between theory, expectations, and reality. So, the aim is to determine the relationship between knowledge competency and understanding of Indonesian language learning personally, professionally, and socially. Quantitative research method with surveys. Sample of 180 people out of 360. Data collection techniques using instruments assisted by Google. Likert Scale Instrument 1-5. 25.0 Statistical analysis techniques, standard deviation, and mean. The mean level of knowledge and understanding of subject content among lecturers is very high. A relationship was found between the three domains of knowledge, understanding, and personal competence. Conclusion: There is a significant relationship between knowledge and understanding of the contents of the personal, professional, and social domains. Keywords: higher education, student competencies, professional and social.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202411